2017
DOI: 10.1098/rspb.2017.0709
|View full text |Cite
|
Sign up to set email alerts
|

Optimal background matching camouflage

Abstract: Background matching is the most familiar and widespread camouflage strategy: avoiding detection by having a similar colour and pattern to the background. Optimizing background matching is straightforward in a homogeneous environment, or when the habitat has very distinct sub-types and there is divergent selection leading to polymorphism. However, most backgrounds have continuous variation in colour and texture, so what is the best solution? Not all samples of the background are likely to be equally inconspicuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 57 publications
5
92
0
Order By: Relevance
“…Michalis et al . (), in field experiments where both humans and avian predators searched for background‐matching artificial prey, showed that the best single camouflage pattern was that of the most likely background sample (where ‘likely’ was quantified using colour and texture modelling of the kind described earlier).…”
Section: Peeling the Onionmentioning
confidence: 98%
See 1 more Smart Citation
“…Michalis et al . (), in field experiments where both humans and avian predators searched for background‐matching artificial prey, showed that the best single camouflage pattern was that of the most likely background sample (where ‘likely’ was quantified using colour and texture modelling of the kind described earlier).…”
Section: Peeling the Onionmentioning
confidence: 98%
“…Michalis et al . () were investigating the situation of a variable, but single type of, background, and infrequent encounters by the predator relative to other prey types. They pointed out that, conversely, if predators learnt the characteristics of a specific pattern through repeated encounters, then negative frequency‐dependent selection would favour polymorphism.…”
Section: Peeling the Onionmentioning
confidence: 99%
“…Maybe the most fundamental strategy to gain protection from predators is via camouflage, which makes prey difficult to detect from its background (Merilaita & Stevens, ). Efficacy of camouflage is always dependent on its visual background (Endler, ; Hughes, Liggins, & Stevens, ; Michalis, Scott‐Samuel, Gibson, & Cuthill, ). Spatial and temporal variation in visual environments (e.g., darkness of the background) can lead to the evolution of color polymorphisms, that is, the coexistence of genetically different color morphs within a population (Bond & Kamil, ; Cook, ; Fisher, ; Ford, ; Roulin, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, part of the human visible spectrum overlaps with the possible visible spectrum from other predators. Thus, mice use part of the visual human spectrum (green and red) to detect potential prays (Denman et al, ), and under certain conditions, birds and humans have shown similar performance in detection tasks (Dukas & Kamil, ; Michalis et al, ). Further studies on predation and escape behavior are needed to test the effectiveness of both coloration cryptic strategies that we suggest in this report.…”
Section: Discussionmentioning
confidence: 99%